How to deliver personalized cardiac resynchronization therapy through the precise measurement of the acute hemodynamic response: Insights from the iSpot trial. - Shun‐Shin, Matthew J.; Miyazawa, Alejandra A.; Keene, Daniel; Sterliński, Maciej; Sokal, Adam; Heuverswyn, Frédéric; Rinaldi, Christopher A.; Cornelussen, Richard; Stegemann, Berthold; Francis, Darrel P.; Whinnett, Zachary (Journal of Cardiovascular Electrophysiology, 2019)
Introduction: New pacing technologies offer a greater choice of left ventricular pacing sites and greater personalization of cardiac resynchronization therapy (CRT). The effects on cardiac function of novel pacing configurations are often compared using multi‐beat averages of acute hemodynamic measurements. In this analysis of the iSpot trial, we explore whether this is sufficient. Materials and Methods: The iSpot trial was an international, prospective, acute hemodynamic trial that assessed seven CRT configurations: standard CRT, MultiSpot (posterolateral vein), and MultiVein (anterior and posterior vein) pacing. Invasive and noninvasive blood pressure, and left ventricular (LV) dP/dtmax were recorded. Eight beats were recorded before and after an alternation from AAI to the tested pacing configuration and vice‐versa. Eight alternations were performed for each configuration at each of the five atrioventricular delays. Results: Twenty‐five patients underwent the full protocol of eight alternations. Only four (16%) patients had a statistically significant >3 mm Hg improvement over conventional CRT configuration (posterolateral vein, distal electrode). However, if only one alternation was analyzed (standard multi‐beat averaging protocol), 15 (60%) patients falsely appeared to have a superior nonconventional configuration. Responses to pacing were significantly correlated between the different hemodynamic measures: invasive systolic blood pressure (SBP) vs noninvasive SBP r = 0.82 (P < .001); invasive SBP vs LV dP/dt r = 0.57, r2 = 0.32 (P < .001). Conclusions: Current standard multibeat acquisition protocols are unfortunately unable to prevent false impressions of optimality arising in individual patients. Personalization processes need to include distinct repeated transitions to the tested pacing configuration in addition to averaging multiple beats. The need is not only during research stages but also during clinical implementation.